Optimale Eigenfinanzierung der Personenunternehmen nach der Unternehmenssteuerreform 2008/2009 - Stefan Homburg; Henriette Houben; Ralf Maiterth (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
Effective from 2008, Germanys top marginal income tax rate rises from 42 to 45 der cent. However, sole proprietorships and partnerships can opt for a preferential tax rate of 28,25 per cent for retained profits (34a EStG-E). If they do so, profits are taxed again upon distribution. Using corporate finance tools we analyse in detail whether or not the option is favourable. However, these tools do nut suffice since the new tax regime is too complicated. Costs of capital cannot be calculated explicitly any more, but we derive exact implicit characterisations. Concrete numerical examples are also provided.
Keywords: M10; H25; D92; 330; Business Taxes; German Income Tax